2001
DOI: 10.1037/0012-1649.37.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Children's responses to same- and other-gender peers: An experimental investigation with 8-, 10-, and 12-year-olds.

Abstract: This research compared how participants in the age range of middle childhood (N = 565, approximate ages 8, 10, and 12 years) resppnded to provocation by a same- or an other-gender peer. In a laboratory play session, participants were provoked in two ways: by losing at a computer game and by being teased by a confederate actor. Immediately following the provoking play session, participants were interviewed about their perceptions of the provoking peer, emotional responses, coping strategies, and social goals. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…The same-gender dyads included here are the same participants from the study and the other-gender dyads are those included in Underwood et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…The same-gender dyads included here are the same participants from the study and the other-gender dyads are those included in Underwood et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…Other times, opposite-sex enmities may be reflective of a polluted social dynamic between the sexes. For example, Underwood, Schockner, and Hurley (2001) placed eight-, ten-, and twelveyear-old children in an experimental scenario where they were teased by either a same-or opposite-sex confederate while losing at a computer game. Observational data taken during the teasing episode indicated that children who were teased by opposite-as compared to same-sex peers showed more negative facial expressions, made more negative remarks, and displayed more negative gestures.…”
Section: Descriptive Characteristics Of Middle Childhood Enemy Relatimentioning
confidence: 99%
“…Gender differences as a function of group composition may be less prevalent in very young populations, similar to the finding in both US and Canadian studies that gender segregation in play increases in prevalence from preschool to elementary school (Maccoby 1988;Serbin et al 1993). Specifically, elementary school children find playing with peers of the opposite gender less pleasing and are likely to behave more negatively toward opposite-gender than same gender peers (Underwood et al 2001). Maccoby (1998) suggests that gender segregation is the result of an incompatibility in play styles.…”
Section: School Levelmentioning
confidence: 98%